Design, synthesis, and biological evaluation of triazole-pyrimidine-methylbenzonitrile derivatives as dual A2A/A2B adenosine receptor antagonists. (31st December 2022) - Li, Zhi; Kou, Lijuan; Fu, Xinzhen; Xie, Zeping; Xu, Maolei; Guo, Lin; Lin, Tiantian; Gong, Shizhou; Zhang, Shumin; Liu, Ming
Abstract: A series of novel dual A2A /A2B AR antagonists based on the triazole-pyrimidine-methylbenzonitrile core were designed and synthesised. The A2A AR antagonist cAMP functional assay results were encouraging for most target compounds containing quinoline or its open-ring bioisosteres. In addition, compound 7i displayed better inhibitory activity on A2B AR (IC50 14.12 nM) and higher potency in IL-2 production than AB928. Moreover, molecular docking studies were carried out to explain the rationality of molecular design and the activity of compound 7i . Further studies on 7f and 7i revealed good liver microsomes stabilities and acceptable in vivo PK profiles. This study provides insight into the future development of dual A2A /A2B AR antagonists for cancer immunotherapy.